2007
DOI: 10.1111/j.1524-4725.2007.33252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Postacne Scarring

Abstract: A requirement for developing successful treatments for postacne scarring is a greater understanding of its pathogenesis, variability among afflicted individuals, and the inflammatory mediators and immunology of the scarring process. Many innovative techniques introduced in the past decade attempt to counteract these pathologic processes while keeping the procedural and postoperative risks to a minimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 105 publications
0
69
0
5
Order By: Relevance
“…In Group B patients -individual scars were marked using a sterile marker pen. 23 gauge needle is inserted adjacent to the scar with the bevel upwards parallel to the skin surface, into the deep dermis under the scar to release fibrous bands at dermal or deep dermal subcutaneous plane (3)(4)(5) by moving needle in horizontal plane using the sharp edge of needle. Post procedure topical antibiotics were given for 5 days along with use of sunscreens (with a minimum sun protection factor of 30 and UVA 3+).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Group B patients -individual scars were marked using a sterile marker pen. 23 gauge needle is inserted adjacent to the scar with the bevel upwards parallel to the skin surface, into the deep dermis under the scar to release fibrous bands at dermal or deep dermal subcutaneous plane (3)(4)(5) by moving needle in horizontal plane using the sharp edge of needle. Post procedure topical antibiotics were given for 5 days along with use of sunscreens (with a minimum sun protection factor of 30 and UVA 3+).…”
Section: Methodsmentioning
confidence: 99%
“…The end result of which is formation of scar tissue. 2,3 Acne scarring is an unfortunate, permanent complication seen in about 95% patients of acne vulgaris up to some degree. 4,5 Given the psychological, social and emotional impact of disfigurement caused due to acne scars, dermatologists are frequently presented with the challenge of evaluating and providing treatment for the same.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Goodman et al observed that once the scar is freed, fat may be satisfactorily injected [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Subcision, also called "subdermal/incisionless undermining", is indicated for the same type of scars that might be improved with fillers or its appearance is improved with manual stretching of the skin during examination [12] . It appears to work by breaking up the attachments of these scars under the skin and releasing the surface from deeper structures [13] . Autologous fat transfer has enjoyed a renaissance in the last several years.…”
Section: Introductionmentioning
confidence: 99%
“…26,28 With this technique, the rolling is usually con nued un l bruising occurs, which ini ates the complex cascade of growth factors that fi nally results in collagen produc on [28][29][30] . Also it provides a clear channel for topical agents to be absorbed more eff ec vely through the top layer of skin.…”
Section: Discussionmentioning
confidence: 99%